Elucidating the role of keratin 75 in enamel using Krt75tm1Der knock-in mouse model - Deshmukh, Rutuja; Vasquez, Brent; Bhogadi, Lasya; Gabe, Claire M.; Lukashova, Lyudmila; Verdelis, Kostas; Morasso, Maria I.; Beniash, Elia (Frontiers in Physiology, 2022)
Keratin 75 (K75) was recently discovered in ameloblasts and enamel organic matrix. Carriers of A161T substitution in K75 present with the skin condition Pseudofollicullitis barbae. This mutation is also associated with high prevalence of caries and compromised structural and mechanical properties of enamel. Krt75tm1Der knock-in mouse (KI) with deletion of Asn159, located two amino acids away from KRT75A161T, can be a potential model for studying the role of K75 in enamel and the causes of the higher caries susceptibility associated with KRT75A161T mutation. To test the hypotheses that KI enamel is more susceptible to a simulated acid attack (SAA), and has altered structural and mechanical properties, we conducted in vitro SAA experiments, microCT, and microhardness analyses on 1st molars of one-month-old WT and KI mice. KI and WT hemimandibles were subjected to SAA and contralateral hemimandibles were used as controls. Changes in enamel porosity were assessed by immersion of the hemimandibles in rhodamine, followed by fluorescent microscopy analysis. Fluorescence intensity of KI enamel after SSA was significantly higher than in WT, indicating that KI enamel is more susceptible to acid attack. MicroCT analysis of 1st molars revealed that while enamel volumes were not significantly different, enamel mineral density was significantly lower in KI, suggesting a potential defect of enamel maturation. Microhardness tests revealed that in KI enamel is softer than in WT, and potentially less resilient to damages. These results suggest that the KI enamel can be used as a model to study the role of K75 in enamel.